Baby's house - McHugh, Gelolo; Blair, Mary 1911-1978 (New York Golden Books, 2012)
See the sights baby sees in the house and the activities done during the day.
"Originally published in slightly different form in the United States by Simon and Schuster, Inc. and Artists and Writers Guild, Inc., New York in 1950"--P. [4] of cover.
Cover title.
On board pages.
UCWS-2014-G-1967 donated by Jan Gabriel M. Castañeda
Keywords: Infants -- Juvenile fiction; Dwellings -- Juvenile fiction; Board books; Children's stories -- Pictorial works